The Role of Social Networking in Capital Sourcing. Issue 2 (April 2022) - Jaiswal-Dale, Ameeta; Simon-Lee, Fanny; Zanotti, Giovanna; Cincinelli, Peter
The aim of this research is to apply the tool of social network analysis to situations in capital sourcing, including early stage financing. The study is conducted within the social network of Medical Alley Association of Minnesota (MAA). We investigate the correlation between the main centrality measures: closeness, degree and betweenness, and the amount of funding received by the 163 MAA members during 2009–2012. Companies benefit from their social network to get access to better financing. The empirical results also provide a road map to encourage the sponsored or spontaneous growth of other social networks in related fields. Despite the financial crisis, the empirical results show how competition works when firms have established relations with others. Where an intersection occurs is merely an empirical curiosity and the causation resides in the intersection of relations. The relation that intersects on an organization determines the player's competitive advantage.